960Dietary intakes of patients with first Acute Coronary Syndrome: the MENZACS study. (2nd September 2021) - Bradbury, Kathryn; Choi, Yeunhyang; Fyfe, Christie; Poppe, Katrina; Rolleston, Anna; Korohina, Erina; Mehta, Suneela; Troughton, Richard; Cameron, Vicky; Porter, Graeme; Kerr, Andrew; Nunn, Chris; et al.
Abstract: Background: In New Zealand (NZ) approximately 10, 000 people experience an acute coronary syndrome (ACS) annually. Little is known about the diets of people who present with first ACS. Methods: The Multi-Ethnic NZ study of Acute Coronary Syndromes (MENZACS) is a multi-centre, longitudinal cohort study of patients with first-time ACS. At baseline, patients complete a validated short food frequency questionnaire (FFQ) asking about dietary intakes in the 12 months preceding their event. Participants are followed up for rehospitalisation and mortality. Results: Here we present the dietary intakes of the 2, 015 participants enrolled into MENZACS. We excluded 90 participants who did not start the FFQ and 42 participants who had extreme energy intakes. For men (n = 1489), the median energy intake was 8637 kJ, and the median percentage of energy from carbohydrate, protein, fat, and saturated fat were 40.3%, 17.9%, 34.7% and 17.8%, respectively. For women (n = 394), the median energy intake was 7499 kJ, and the median percentage of energy from carbohydrate, protein, fat and saturated fat were 40.3%, 18.4%, 35.6%, and 18.0%, respectively. Conclusions: Both men and women reported high saturated fat intakes in the year preceding their first ACS. Future work will examine dietary predictors of rehospitalisation and mortality, as well as analyse baseline blood samples for Lipoprotein(a) and lipidomics. Key messages: Patients in hospital with first time ACS are able to complete a short food frequency questionnaire, with little missing data.